Festival Breves Cenas De Teatro: um evento contemporâneo em Manaus. - Virgílio, Tiziane Assunção (2018)
This research, which is written in the first person, is a case study on The Festival Breves Cenas de Teatro – a short scene Festival with scenes up to fifteen minutes of duration. A contemporary event, with eight editions held since 2009. This dissertation focuses on the contemporaneity of events and addresses questions about the instantaneity of time and of the time of the scene; historical, cultural and political aspects of the city of Manaus and the Brazilian state, Amazonas; academic qualification in training professionals for areas like culture, culture management, marketing strategies, and the relationships between consuming and public policies. All this is done through participant observation, interviews, bibliographic research, and statistics analysis. Introducing an overview of all Festival Breves Cenas de Teatro editions in Manaus, from its beginnings to future prospects.